Manejo agronómico del cultivo de abacá (Musa textilis) en Ecuador - Yaguachi Andrade, Fiorela Mabel (2024)
Abaca (Musa textilis) is a natural fiber of great importance worldwide, with the Philippines being the main producer and exporter. Ecuador, due to its diversity of regions and climates, stands out as the main producer of abaca fiber. Abaca production is concentrated in certain areas of the country, generating employment and improving living conditions in local communities. This research aimed to determine the agronomic management of abaca (Musa textilis) cultivation in Ecuador. The methodology used was through the analysis technique, magazines, current texts, articles, synthesis and summary of the collected data. The results reveal the importance of agronomic practices for the successful cultivation of abaca, highlighting the need for soil preparation, quality seed selection, pest and disease control, and sustainable practices. Furthermore, the geographic analysis shows a significant concentration of the crop in specific regions of Ecuador, highlighting the adaptation of agronomic practices to the unique characteristics of each region. In conclusion, abaca agronomic practice focuses on comprehensive techniques that guarantee successful and sustainable cultivation, with emphasis on the quality of the resistant fiber. The implementation of good agronomic management benefits farmers and highlights the importance of sustainable practices. This crop is concentrated in the provinces of Manabí, Los Ríos and Pichincha, benefiting from optimal climatic and soil conditions, providing an accurate view of the activity. abaca agriculture in the country.